Effects of interpersonal familiarity on the auditory distance perception of level-equalized reverberant speech - Demirkaplan Özgen; Hacıhabiboğlu Hüseyin (Acta Acustica, 2020)
Familiarity with sound sources is known to have a modulatory effect on auditory distance perception. However, the level of familiarity that can affect distance perception is not clearly understood. A subjective experiment that aims to investigate the effects of interpersonal familiarity on auditory distance perception with level-equalized stimuli is reported. The experiment involves a binaural listening task where different source distances between 0.5 and 16 m were emulated by convolving dry speech signals with measured binaural room impulse responses. The experimental paradigm involved level-equalized stimuli comprising speech signals recorded from different-gender couples who have self-reported to have known each other for more than a year with daily interaction. Each subject judged the distances of a total of 15 different speech stimuli from their partner as well as spectrally most similar and most dissimilar strangers, for six different emulated distances. The main finding is that a similar but unfamiliar speaker is localized to be further away than a familiar speaker. Another finding is that the semantic properties of speech can potentially have a modulating effect on auditory distance judgements.